Supply Chain Information Operation Model for Lifelong Learning in the National Credit Bank Format - Artaphon Chansamut (ExcelingTech, 2023)
The objectives of this research to develop supply chain information operation model for lifelong learning in the national credit bank format and to evaluate the model The sample groups were ten experts in supply chain. The research tool was evaluation form to evaluate supply chain information operation model for lifelong learning in the national credit bank format comprises five main components, namely Suppliers, Manufacturer, education customers and The data analysed by using arithmetic mean and standard deviation The overall evaluation result about supply chain information operation model for lifelong learning in the national credit bank format was a high level. suggesting that supply chain information operation model for lifelong learning in the national credit bank format to support sustainable Information system development.